2019
DOI: 10.1039/c9nj00323a
|View full text |Cite
|
Sign up to set email alerts
|

Turn-on fluorescent sensor for the detection of lipopolysaccharides based on a novel bispyrenyl terephtalaldehyde-bis-guanylhydrazone

Abstract: A “turn-on” bispyrenyl sensor for lipopolysaccharide detection with unique molecular conformations exhibits excimer emission with sensitivity down to nanomolar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…[38] These effects on unsaturated aliphatic, aromatic and heterocyclic compounds were theoretically examined by a combination of second order Møller-Plesset perturbation theory (MP2) and hybrid density functional M06-2X. [39] The M06 functionals [40] developed by the Truhlar group had also been successfully used for studying adsorption and reactions on acidic Zeolites [39,41,42], on Lewis-acid zeolites [43,44], on metallic catalysts [45][46][47][48][49], and on organic molecules [50,51]. Recently they have been applied to determine P-NMR chemical shifts of phosphorus-modi ed CHA zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…[38] These effects on unsaturated aliphatic, aromatic and heterocyclic compounds were theoretically examined by a combination of second order Møller-Plesset perturbation theory (MP2) and hybrid density functional M06-2X. [39] The M06 functionals [40] developed by the Truhlar group had also been successfully used for studying adsorption and reactions on acidic Zeolites [39,41,42], on Lewis-acid zeolites [43,44], on metallic catalysts [45][46][47][48][49], and on organic molecules [50,51]. Recently they have been applied to determine P-NMR chemical shifts of phosphorus-modi ed CHA zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42] It is also used as a probe in chemosensors that detect particular metal ions [43][44][45][46][47][48][49][50][51] and molecules. [52][53][54][55] The properties of an excimer are closely related to those of the monomer. [56][57][58] Thus, the excited states of pyrene and its derivatives have been vigorously investigated and still continue to attract much interest from scientists with respect to both fundamental studies and practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Many nonenzymatic methods were thus developed to detect LPS, including electrochemical, surface plasmon resonance (SPR), colorimetric, and fluorescent sensors. However, the electrochemical and SPR sensors frequently suffer from high requirements for electrode and chip preparation, while the sensitivity of colorimetric sensors makes it difficult for them to meet the clinical requirements. In contrast, fluorescent probes have the advantages of easy operation, online detection, and high sensitivity, showing great potential in LPS detection. For examples, Wu et al prepared a peptide-functionalized polydiacetyl liposome-based fluorescence turn-on sensor to detect LPS at micromolar concentration. Wang et al reported an alkylated ammonium-pyrene probe for LPS detection at a limit of detection (LOD) of 100 nM .…”
Section: Introductionmentioning
confidence: 99%